Lactylated Histone H3K18 as a Potential Biomarker for the Diagnosis and Predicting the Severity of Septic Shock - Chu, Xin; Di, Chenyi; Chang, Panpan; Li, Lina; Feng, Zhe; Xiao, Shirou; Yan, Xiaoyu; Xu, Xiaodong; Li, Hexin; Qi, Ruomei; Gong, Huan; Zhao, Yanyang; et al. (Frontiers in Immunology, 2022)
Objective To date, there are no studies regarding the lactylation profile and its role in critically ill patients. Thus, we aimed to examine expression of histone H3 lysine 18 (H3K18) lactylation and its role in patients with septic shock. Methods Thirteen healthy volunteers and 35 critically ill patients from the Department of Surgical Intensive Care Medicine, Beijing Hospital were enrolled in our study. Baseline information and clinical outcomes were obtained prospectively. Lactylation levels of all proteins and H3K18 from peripheral blood mononuclear (PBMC) were determined by western blotting and serum levels of inflammatory cytokines by flow cytometry. Arginase-1 (Arg1) and Krüppel-like factor-4 (Klf4) mRNA expression was evaluated by quantitative real-time PCR (qRT-PCR). Results Lactylation was found to be an all-protein post-translational modification and was detected in PBMCs from both healthy volunteers and critically ill patients, with a significantly higher relative density in shock patients (t=2.172, P=0.045). H3K18la was expressed in all subjects, including healthy volunteers, with the highest level in septic shock patients (compared with non-septic shock patients, critically ill without shock patients and healthy volunteers P=0.033, 0.000 and 0.000, respectively). Furthermore, H3K18la protein expression correlated positively with APACHE II scores, SOFA scores on day 1, ICU stay, mechanical ventilation time and serum lactate (ρ=0.42, 0.63, 0.39, 0.51 and 0.48, respectively, ρ=0.012, 0.000, 0.019, 0.003 and 0.003, respectively). When we matched patients with septic shock and with non-septic shock according to severity, we found higher H3K18la levels in the former group (t=-2.208, P =0.040). Moreover, H3K18la exhibited a close correlation with procalcitonin levels (ρ=0.71, P=0.010). Patients with high H3K18la expression showed higher IL-2, IL-5, IL-6, IL-8, IL-10, IL-17, IFN-α levels (ρ=0.33, 0.37, 0.62, 0.55, 0.65, 0.49 and 0.374 respectively, P=0.024, 0.011, 0.000, 0.000, 0.000 and 0.000 respectively). H3K18la expression also displayed a positive correlation with the level of Arg1 mRNA (ρ=0.561, P=0.005). Conclusions Lactylation is an all-protein post-translational modification occurring in both healthy subjects and critically ill patients. H3K18la may reflect the severity of critical illness and the presence of infection. H3K18la might mediate inflammatory cytokine expression and Arg1 overexpression and stimulate the anti-inflammatory function of macrophages in sepsis.